Decreased quality and off-flavour compound accumulation of 3–10 kDa fraction of pine nut (Pinus koraiensis) peptide during storage. (October 2017) - Lin, Songyi; Yang, Ruiwen; Cheng, Sheng; Wang, Ke; Qin, Lei
Abstract: Pine nut peptide possesses good antioxidant activity. But the research related to the decreased quality and the development of off-flavour during storage is limited. In the present study, a 3–10 kDa fraction of pine nut ( Pinus koraiensis ) peptide (PNP3–10 kDa ) was prepared by enzymolysis and ultrafiltration. Thereafter, PNP3–10 kDa was stored for 30 days at 75% relative humidity and 25 °C. Changes in DPPH radical scavenging capacity, secondary structure (by FT-MIR), surface structure (by SEM) and volatile compounds (by SPME-GC-MS) were measured at various time intervals over thirty days. Results showed that the DPPH radical scavenging capacity decreased from 76.91% ± 0.49% to 40.50% ± 0.84% with the accumulation of volatile compounds. The secondary structure and surface structure was not changed. However, the form and size of PNP3–10 kDa particle were changed dramatically during the storage. In total 15 volatile compounds were identified during the storage. The intensity of volatile compounds presented dynamic changes. 2-Ethylhexyl acetate and pyrazines were mainly formed through esterification and Maillard reaction. The reactions appeared to be strongest by the sixth day. Principal component analysis (PCA) indicated that 30 days' storage could cause remarkable changes to the volatile compounds. Highlights: The PNP3–10kDa 's quality changes for 30 storage days were detected firstly. Differences in 30 storage days were determined by FT-MIR, SEM and SPME-GC-MS. 2-Ethyl-1-hexanol, dibutyl phthalate and pyrazines had the strongest reaction in 6th day. Esterification was discovered and the formation of pyrazines was speculated.